Investigating local governments a manual for reporters - Balgos, Cecile C.A (Philippine Center for Investigative Journalism, 2001)
A publication that provides journalists with a local-governance roadmap to guide them in their day-to-day coverage of news. It contains information about governance at the local level - what is it all about and several new ways on how reporters can deal with it.